Climate policy and dependence on traded carbon - Andrew, Robbie M; Davis, Steven J; Peters, Glen P (Environmental research letters, 2013)
A growing number of countries regulate carbon dioxide (CO2) emissions occurring within their borders, but due to rapid growth in international trade, the products consumed in many of the same countries increasingly rely on coal, oil and gas extracted and burned in other countries where CO2 is not regulated. As a consequence, existing national and regional climate policies may be growing less effective every year. Furthermore, countries that are dependent on imported products or fossil fuels are more exposed to energy and climate policies in other countries. We show that the combined international trade in carbon (as fossil fuels and also embodied in products) increased from 12.3 GtCO2 (55% of global emissions) in 1997 to 17.6 GtCO2 (60%) in 2007 (growing at 3.7% yr−1). Within this, trade in fossil fuels was larger (10.8 GtCO2 in 2007) than trade in embodied carbon (6.9 GtCO2), but the latter grew faster (4.6% yr−1 compared with 3.1% yr−1 for fuels). Most major economies demonstrate increased dependence on traded carbon, either as exports or as imports. Because energy is increasingly embodied in internationally traded products, both as fossil fuels and as products, energy and climate policies in other countries may weaken domestic climate policy via carbon leakage and mask energy security issues.